Attitude Factor in Increasing Intention to Come to The Integrated Service Post - Suparji, Suparji; Surtinah, Nani; Nugroho, Heru Santoso Wahito; Sunarto, Sunarto (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Integrated Healthcare Center (integrated service post) is the government's effort to make it easier for the Indonesian people to obtain maternal and child health services. The main problem of this research is the low number of visits by toddlers to Integrated Healthcare Center service posts. This study analyses the relationship between attitudes about the Integrated Healthcare Center and intention to come to the Integrated Healthcare Center. The researcher wants to apply the theory of planned behaviour that intentions influence behaviour while attitudes towards an object, subjective norms and behavioural control influence intentions. Rangacanga correlation research, with a cross-sectional approach. The population of mothers under five is 135 people, and the sample size is 101 people. The sampling technique used is simple random sampling. The data collection instrument was in the form of attitude and intention questionnaires. The independent variable is attitude, and the dependent variable is the intention to visit the Integrated Healthcare Center. In statistical analysis with the Pearson product-moment statistical test, the error rate is set at 0.05. The results showed that 51.28% of mothers under five had a positive attitude, and 51.28% had positive intentions. Statistical test results obtained p: 0.00 <α 0.05 concluded that there is a relationship with the correlation coefficient value of 0.670. This study concludes that the mother's positive attitude positively impacts Integrated Healthcare Center visits by mothers of toddlers. So, it is suggested that community leaders or health workers motivate and empower the community to participate in Integrated Healthcare Center activities.